Geochemical characteristics of rare earth elements in different types of soil: A chemometric approach - Khan, A.M.; Behkami, S.; Yusoff, Ismail; Zain, Sharifuddin Md; Bakar, Nor Kartini Abu; Bakar, Ahmad Farid Abu; Alias, Yatimah (Elsevier, 2017)
Rare earth elements (REEs) are becoming significant due to their huge applications in many industries, large-scale mining and refining activities. Increasing usage of such metals pose negative environmental impacts. In this research ICP-MS has been used to analyze soil samples collected from former ex-mining areas in the depths of 0–20 cm, 21–40 cm, and 41–60 cm of residential, mining, natural, and industrial areas of Perak. Principal component analysis (PCA) revealed that soil samples taken from different mining, industrial, residential, and natural areas are separated into four clusters. It was observed that REEs were abundant in most of the samples from mining areas. Concentration of the rare elements decrease in general as we move from surface soil to deeper soils.